The role of mitochondrial dysfunction in the cytotoxic synergistic effect of gemcitabine and arsenic on breast cancer - Farshid Maleki; Somayeh Handali; Mohsen Rezaei (PLoS ONE, 2025)
Breast cancer is the most common type of cancer in women worldwide. A common approach to cancer treatment in clinical practice is to use a combination of drugs to enhance the anticancer activity of drugs while reducing their side effects. In this regard, we evaluated the effectiveness of combined treatment with gemcitabine (GCB) and arsenic (ATO) and how they affect the cell death pathway in cancer cells. Cytotoxic activity of drugs individually or combined against MDA-MB-231 and MCF-7 was performed by MTT method and isobolographic analysis was used to determine the interaction between these factors. The combination of ATO and GCB showed synergistic anti-cancer activity (CI < 1) in both cancer cell lines. The combination of ATO and GCB induced sub-G1 phase arrest, apoptosis and death rates in MCF-7 and MDA-MB-231 cells. The apoptotic response induced by the combination of GCB and ATO was dependent on caspase 3/7. Combined treatment with mitochondrial membrane potential (MMP) reduction and increased reactive oxygen species (ROS) production caused mitochondrial dysfunction. Co-treatment significantly reduced catalase (CAT) activity in both cancer cells compared to the control group and cells treated with each monotherapy. A significant decrease in cellular GSH was observed in cancer cells treated with ATO and GCB. In addition, migration and invasion were significantly reduced in breast cancer cells treated with the combination of ATO and GCB compared to cells treated with ATO and GCB. In conclusion, the combined treatment of ATO and GCB synergistically increased the anti-cancer activity, and these findings provide an effective approach for the treatment of breast cancer. To the best of our knowledge, this is the first study showing promising results for combination therapy with ATO and GCB in breast cancer.